Polymerization Cycle and Occlusal Vertical Dimension of Complete Dentures: Systematic Review and Meta-Analysis - Quintella, Melanie Calheiros Miranda; Pellizzer, Eduardo Piza; Vasconcelos, Belmiro Cavalcanti do Egito; Lemos, Cleidiel Aparecido Araújo; Gomes, Jéssica Macela Luna; Costa, Rayanna Thayse Florêncio; Fernandes e Oliveira, Hiskell Francine; Lopes, Leonardo Ferreira de Toledo Piza; Moraes, Sandra Lúcia Dantas de (ARCHIVES OF HEALTH INVESTIGATION, 2023)
The aim of this systematic review and meta-analysis was to assess the influence of the polymerization cycle on the occlusal vertical dimension (OVD) of complete dentures. This review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The PICO (Population, Intervention, Comparison, Outcome) question evaluated was “Does the microwave polymerization cycle influence the occlusal vertical dimension of complete dentures when compared to conventional water bath polymerization?”. The literature search was conducted in the PubMed/MEDLINE, Web of Science, and Scopus databases for relevant articles published up to March 2023. In vitro studies involving OVD measurement from complete dentures polymerized with different polymerization methods were included. The risk of bias was analyzed using the Critical Appraisal Checklist for Quasi-Experimental Studies (non-randomized experimental studies) from the Joanna Briggs Institute (JBI). The meta-analysis was based on the inverse variance (IV) methods with mean difference (MD) for OVD evaluation between techniques. Five articles were included in the qualitative and quantitative analysis. A total of 222 complete dentures were evaluated. In the polymerization cycles, microwave cycles with 90 W to 810 W between 3-5 minutes and conventional water bath cycles between 9-12 hours (long cycles) and 3-4 hours (short cycles) were used. In a quantitative analysis of polymerization methods, no statistically significant difference was found between water bath and microwave techniques [p = 0.99; MD: -0.00; CI = -0,26-0,26]. The current meta-analysis can be concluded that both techniques can be used to polymerization of complete dentures without significant clinical changes in the OVD.